On the rotation of supermassive stars - Haemmerlé, Lionel; Woods, Tyrone E.; Klessen, Ralf S.; Heger, Alexander; Whalen, Daniel J. (The astrophysical journal. Part 2, Letters, 2018)
Supermassive stars (SMSs) born from pristine gas in atomically cooled halos are thought to be the progenitors of supermassive black holes at high redshifts. However, the way they accrete their mass is still an unsolved problem. In particular, for accretion to proceed, a large amount of angular momentum has to be extracted from the collapsing gas. Here, we investigate the constraints stellar evolution imposes on this angular momentum problem. We present an evolution model of a supermassive Population III star simultaneously including accretion and rotation. We find that, for SMSs to form by accretion, the accreted angular momentum has to be about 1% of the Keplerian angular momentum. This tight constraint comes from the limit, at which the combination of radiation pressure and centrifugal force cancels gravity. It implies that SMSs are slow rotators, with a surface velocity less than 10%-20% of their first critical velocity, at which the centrifugal force alone cancels gravity. At such low velocities, the deformation of the star due to rotation is negligible.
Gesehen am 19.08.2019